Improvement of methodological approaches for the determinationof specific and volumetric activities of 90Sr in feeds, food products, animal foods and water - Straliayeva, Zoya; Bardyukova, Alesya V. (Journal of the Belarusian State University. Ecology, 2026)
Delivery of scientific and methodological follow-up shall be based on the method’s most recent revised edition, unless its use is deemed unreasonable or impossible. When necessary, additional clarifications should be developed to put it to practice and ensure the method’s consistency. According to GOST ISO/IEC 17025-2019, a number of measurement procedures used in scientific research, monitoring practices and audits are subject to improvement, with subsequent verification and validation. Such are, for instance, the Guidelines for Radiochemical Methods of Determining Radioactivity in Veterinary Facilities, approved by General Veterinary Office, USSR Ministry of Agriculture, of August 24, 1984, Moscow. Existing methodological guidelines and recommended practices require further modernization and upgrade of the basic measurement approaches, as well as validation and verification of data. By establishing and introduction of scientific and organizational basics, technical means, rules and standards, required for laboratory research, one might expect a definitely high economical effect achieved through shifting from outdated procedure to an updated and improved one. The document’s development was preceded by radiochemical analysis sequence revision: the process of radionuclide extraction from raw and concentrated feeds via oxalate procedure. Specified and adjusted are the sequence and scope of operations at preparation and implementation stages, including operational and environmental safety and operators’ qualification requirements. The sequential steps of radiochemical analysis include converting of samples into a solution, isolation of the radionuclide, its radiometry with subsequent statistical processing of the results obtained. The methodological approaches used for the determination of plutonium in soil should take into account both the individual characteristics of samples and the nature of their radioactive contamination. The procedure contains all structural elements in accordance with Gosstandard Decree No. 61 of July 1, 2021, which replaced the existing GOST 8.010-2013 for authoring measurement procedures. The methodology includes the uncertainty assessment developed by us for this analytical method. The methods for determining radionuclides in the environment are used to ensure strict compliance with the safety requirements for foodstuffs, water, and feedstuffs in fee production sectors. As of today, there exist certain regulatory documentation but no methods of how to determine the limit exceedance in the field of radiology, or the methods are outdated or do not have the lawful certification by an authorized metrological agency.
Keywords: radiochemical analysis; radiochemical isolation; phosphate method; oxalate method; samples; 90Sr